Sharia Supervisory Board and Islamic Banking Performance in Indonesia: Does Size Matter? - Pessiwarisa, Jerry Adriaan; Kasri, Rahmatina Awaliyah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2025)
Research Originality: This study is amongst a few studies empirically examining the impact of the Sharia Supervisory Board's (SSB) characteristics on the financial performance of Islamic banks in Indonesia. This attribute concerns regulators and market players due to its importance in Shariah governance and Islamic banks' performance. This study encompasses both full-fledged and dual-banking Islamic financial institutions.Research Objectives: This study investigates the impact of the Sharia Supervisory Board's characteristics on the financial performance of Islamic banks in Indonesia.Research Methods: This study utilizes random-effects GLS unbalanced panel data regression analysis with panel data from 30 Islamic banks in Indonesia (13 full-fledged Islamic banks and 17 dual-banking Islamic banks) from 2018 to 2023.Empirical Results: The study highlights the pivotal role of SSB size in enhancing the financial performance of Islamic banks. The results suggest that the size of SSB has a significant positive influence on the financial performance of Islamic banks in Indonesia during the 2018- 2023 period.Implications: It provides additional rationale for the newly issued regulation regarding the SSB size in Indonesia. It also offers actionable insights into the necessity of effective governance structures to ensure the sustainable growth of Islamic banking institutions.JEL Classification: G21, G28, G34How to Cite:Pessiwarisa, J. A., & Kasri, R. A. (2025). Sharia Supervisory Board and Islamic Banking Performance in Indonesia: Does Size Matter?. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 231-246. https://doi.org/10.15408/sjie.v14i1.44740.